Was Weber Right? The Effects of Pay for Ability and Pay for Performance on Pro-Social Motivation, Ability and Effort in the Public Sector - Banuri, Sheheryar (The World Bank, 2015)
This paper examines the effects of pecuniary compensation on the ability and motivation of individuals in organizations with non-pecuniary or pro-social missions. In particular, the paper compares flat pay systems, unrelated with ability or effort, to two other systems that are considered superior: high-powered, pay for performance schemes and more traditional, "Weberian" schemes that calibrate pay to ability, independent of effort. The analysis uses a sample of future public sector workers and finds that all three pay schemes attract motivated workers into tasks with a pro-social mission. However, flat pay schemes also attract low ability workers. In the short run, pay-for-performance schemes generate higher effort than flat pay and pay-for-ability systems, a difference driven entirely by effects on unmotivated workers. Once selection effects are accounted for, however, workers with pay for ability and pay for performance exert statistically indistinguishable levels of effort in the pro-social task. Moreover, pay for ability elicits effort at lower cost than pay for performance